2007
DOI: 10.1021/jp066348j
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanism of Silicon Etching in HNO3-Rich HF/HNO3 Mixtures

Abstract: The wet chemical etching of silicon using HNO 3 -rich HF/HNO 3 mixtures has been studied. The effect of different parameters on the etch rate of silicon, for example, the HF/HNO 3 mixing ratio, the silicon content of the etchant, temperature, and stirring speed in these solutions, has been examined and discussed in light of a previous study on etching in HF-rich HF/HNO 3 mixtures. Nitrogen(III) intermediates are generated owing to the dissolution of silicon and the decomposition if the solution is exposed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 35 publications
6
122
0
Order By: Relevance
“…13 To replace nitric acid, alternative oxidants as ammonium peroxodisulfate (NH 4 ) 2 S 2 O 8 , ozone O 3 , and hydrogen peroxide H 2 O 2 were tested. 1,[14][15][16] In these solutions the reactivity is very low, for example in HF-O 3 -mixtures a dissolution rate of silicon of 0.6 nm s −1 is observed.…”
mentioning
confidence: 99%
“…13 To replace nitric acid, alternative oxidants as ammonium peroxodisulfate (NH 4 ) 2 S 2 O 8 , ozone O 3 , and hydrogen peroxide H 2 O 2 were tested. 1,[14][15][16] In these solutions the reactivity is very low, for example in HF-O 3 -mixtures a dissolution rate of silicon of 0.6 nm s −1 is observed.…”
mentioning
confidence: 99%
“…On the one hand, recent studies have shown [8] that during the etching in acid mixtures, the injection of holes into semiconductor valence band occurs due to reduction of nitric acid on Si surface. This process indicates the electrochemical origin of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…However, several further species including NO2, N2O, and H2 were detected as additional reaction products of HF-HNO3-H2O etching solutions [6,7], and the formation of an intermediate silicon dioxide layer was excluded by means of XPS measurements [8,9]. Instead, after etching in HF-containing solutions silicon surfaces are completely hydrogen-terminated, and in a few cases F atoms have been detected on the silicon surface.…”
Section: Introductionmentioning
confidence: 99%